ANALYSIS OF THE LEADERSHIP OF FEMALE SCHOOL PRINCIPLES IN INCREASING THE QUALITY OF EDUCATORS AND STUDENTS AT MADRASAH IBTIDAIYAH - Muhsin, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This paper describes how the implementation of women's leadership management to improve the quality of educators and students at MIN 2, Maron sub-district, Probolinggo district. This research use desciptive qualitative approach. Based on the presentation and analysis of the data, conclusions can be drawn, among others; (1) the leadership style of the principal at MIN 2 Probolinggo is based on practice and exemplary religious-socialist doctrine; (2) the improvement in the quality of students is evident in the various achievements obtained by MIN 2 Probolinggo, such as innovation in the field of religion, adiwiyata and literacy and the pioneering of 'child- friendly' madrasas. In fact, in the past year, there have been at least 19 educator and student achievements for 2022 and 4 achievements at the beginning of 2023; (3) the quality of schools can also be seen from the high appreciation from various groups such as the Probolinggo district Ministry of Religion and the East Java Regional Office in the field of religious innovation, UNESA universities in terms of literacy, the Probolinggo district environmental service (DLH) in terms of adiwiyata and support from various parties particularly relevant to the parents of students; (4) MIN 2 Probolinggo also declared "Child Friendly" madrasas as a representation of the concern of educational institutions that fulfill the rights and protection of children; and (5) an intensive evaluation is carried out by the principal by involving professional and competent parties in their fields. Especially in evaluating the five aspects of discipline, infrastructure, self-development, financing and innovative learning processes